(untitled) (Faridpur Medical College Journal, 2021)
Postpartum Acute Kidney Injury (AKI) is one of the serious complications of pregnancy and is associated with high mortality and morbidity. Although Postpartum AKI has decreased markedly in developed countries in the last 50 years, but it is a challenging health problem in pregnant women, specially in the developing countries like Bangladesh. Aim of this study was to determine the contributing factors and outcome of postpartum AKI. This observational study was conducted in the department of nephrology, Faridpur Medical College Hospital from January 2018 to December 2019. During that study period thirty two patients with postpartum AKI were admitted in the above mentioned department. Demographic, clinical and laboratory data of those patients were recorded. Mean age of patients was 25.3 ± 4.2 years, and the 72% patients underwent cesarean section. Oliguria was the main presentation (91%). Puerperal sepsis (38%), postpartum hemorrhage (22%), and Eclampsia (16%) were the common contributing factors. Hemodialysis was required for most of the patients (75%). Therefore early diagnosis, identification and treatment of cause, timely initiation of renal replacement therapy is mandatory. Faridpur Med. Coll. J. 2020;15(2): 62-64